2006
DOI: 10.1039/b610208e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-containing carbon nanotubes as solid base catalysts

Abstract: Nitrogen-containing carbon nanotubes (NCNT) are effective re-usable solid base catalysts, their activity for a Knoevenagel condensation being related to the amount of pyridinic nitrogen incorporated in the NCNT structure, which could be tuned by the synthesis parameters of the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
162
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(167 citation statements)
references
References 28 publications
3
162
0
2
Order By: Relevance
“…Besides serving as a support, CNTs alone can be used as catalysts for some specific reactions, including methane and NO x decomposition [3,4], oxidative dehydrogenization of aromatic hydrocarbons and alkanes [5,6,7,8,9], oxidation of aniline [10], p-toluidine [11], and benzyl alcohol [12], catalytic wet air oxidation of phenol [13,14] and pcoumaric acid [15,16], aerobic oxidation of cyclohexane [17,18], ozonation of oxalic acid [19,20], selective oxidation of H 2 S [21], and heterogeneous hydroxylation of organics [22]. Nitrogen-doped CNTs were used as basic catalyst in Knoevenagel condensation [23] and CO oxidation [24] reactions. Based on these results, it is very reasonable to conclude that CNTs can serve as an excellent heterogeneous catalyst having (1) the potential to form a macrostructured catalyst of sufficient mechanical strength; (2) a tunable morphology and surface chemistry for enhanced catalytic activity and selectivity; (3) high surface area and specific porosity; (4) good thermal stability and resistance against acidic/basic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Besides serving as a support, CNTs alone can be used as catalysts for some specific reactions, including methane and NO x decomposition [3,4], oxidative dehydrogenization of aromatic hydrocarbons and alkanes [5,6,7,8,9], oxidation of aniline [10], p-toluidine [11], and benzyl alcohol [12], catalytic wet air oxidation of phenol [13,14] and pcoumaric acid [15,16], aerobic oxidation of cyclohexane [17,18], ozonation of oxalic acid [19,20], selective oxidation of H 2 S [21], and heterogeneous hydroxylation of organics [22]. Nitrogen-doped CNTs were used as basic catalyst in Knoevenagel condensation [23] and CO oxidation [24] reactions. Based on these results, it is very reasonable to conclude that CNTs can serve as an excellent heterogeneous catalyst having (1) the potential to form a macrostructured catalyst of sufficient mechanical strength; (2) a tunable morphology and surface chemistry for enhanced catalytic activity and selectivity; (3) high surface area and specific porosity; (4) good thermal stability and resistance against acidic/basic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Here we determined the total amount of surface sites by deconvolution of proton uptake curves which were derived from titration curves. This technique provides more detailed information about the pK a distribution of the accessible sites than can obtained from titration curves alone as was done before [27]. The site density of the NCNT is about an order of magnitude lower compared to the site density of AC-SAsuper samples and, although acidic, the site density of CNF OX .…”
Section: Resultsmentioning
confidence: 93%
“…As test reaction to analyse the NCNT's catalytic activity we chose the Knoevenagel condensation of benzaldehyde (BA) with ethylcyanoacetate (ECA) resulting in ethyl-a-cyanocinnamate (ECC) (Scheme 1.) In a preliminary study we showed that the pyridinic nitrogen atoms present in the NCNT were responsible for the catalytic activity [27]. Here we report a more detailed study on a kinetic analysis, including product inhibition and mass transfer limitation, of the above mentioned Knoevenagel condensation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon materials are known to act as an effective catalyst in several organic and pyridine on supported metal particles [5]. They showed that these nitrogen-doped carbon materials were active for Knoevenagel reactions.…”
Section: Introductionmentioning
confidence: 99%